(untitled) (Medicine Today, 2021)
Introduction: This study has been designed to evaluate the success rate of closed reduction and stabilization by two lateral parallel percutaneous K-wires with the help of C-arm in the management of Gartland type-III closed supracondylar fracture of humerus in children. Materials and Methods: A prospective quasi experimental study was conducted from January 2015 to December 2016 in NITOR. A total of 30 patients of Gartland type-III closed supracondylar fracture of humerus in children presenting between ages 3-12 years. Informed written consent was taken from patient’s guardian. Regular follow up was targeted for at least 6 month’s. Result was evaluated according to Flynn’s grading. Results: Mean age was 6.85± 2.37 years, number of patients ware 30, Male patients were more affected 22 (73.33%) than female 8(26.67%), left side patients were more affected. Mean loss of elbow flexion was 9.53 degrees, mean loss of carrying angle was 8.5 degrees. Complications included four (13.33%) cases of pin tract infection, four (13.33%) cases of fracture blister, one (3.33%) case of median nerve palsy, two (6.66%) cases of inadequate pin fixation at first attempt. There were six excellent (20%), eighteen good (60%), three (10%) fair and three (10%) poor results according to Flynn’s grading. The overall 90% satisfactory result and rest 10% unsatisfactory result. Conclusion: Closed reduction and stabilization by two lateral parallel percutaneous K-wires is a better method for treatment of Gartland type-III closed supracondylar fracture in children. Medicine Today 2021 Vol.33(2): 138-142